(untitled) (UNED Research Journal, 2016)
African star grass is important in some tropical regions and can benefit from the use of biofertilizers like Azospirillum. We tested three strains of Azospirillum as biofertilizer in Turrialba, Costa Rica, from 2011 through 2013. A single dose of 5 liters per hectare was used for the three strains (108 CFC.ml-1) and a three-way mixture of the strains; and compared with a dose of 10 tons of vermicompost and chemical fertilization (78 kg N per hectare). A second experiment evaluated Azospirillum for its potential to substitute chemical fertilizer in proportions of 0, 25, 50 and 75%. A dose of 5 L/ha (108 CFU.ml-1) was used for all treatments and compared to the dose of 100% of chemical fertilizer. Two of the strains and the three-way yielded similar forage biomass (3.65 to 3.93 t/ha) as the chemical fertilizer (4.12 t/ha). Fertilization with vermicompost was lower (3.56 t/ha). A decline in rainfall from 2012 to 2013 reduced the grass biomass 25% when chemical fertilization was applied (4.07 vs 3.08 t/ha). In the second experiment, no significant differences were found in biomass yields for all treatments with Azospirillum or chemical fertilizer (2.97 vs 3.08 t/ha). Azospirillum has potential to maintain the productivity of African star grass under a grazing system, but further research is required to define the number of applications per year to maintain a constant effect.